Under the yoga mat: the dark history of Yogi Bhajan's Kundalini yoga - Coenen, Els (Izzard Ink Publishing, 2023)
"Let's face and share the pain. Els Coenen's groundbreaking exposé, Under the Yoga Mat, lifts the veil on the underexposed dark side of the history of Yogi Bhajan's Kundalini Yoga and his revered 3HO Healthy, Happy, Holy community. This is the first book presenting the multifaceted character and extent of the wrongdoings and the tactics used by 3HO leadership to keep the horrific abuse hidden for five decades. This meticulously researched non-fiction work delves deep into the disturbing tragedies that unfolded when Harbhajan, a 39-year-old Sikh-born Indian customs officer, arrived in Los Angeles in 1968, posing as a master of Kundalini Yoga. Through a thoughtful selection of testimonies, historical records, and expert insights, Coenen unravels the captivating rise of Yogi Bhajan, as disillusioned American youth eagerly embraced him as the Eastern guru they believed they needed. As his following grew rapidly, he wove a narrative of destiny, proclaiming that his devotees were predestined to guide humanity in the transition from the Piscean to the Aquarian Age. Yet, behind the facade of spiritual enlightenment, Bhajan cunningly manipulated, controlled, exploited, and abused his followers and their children. He was involved in drug and arms smuggling and fraudulent businesses. Throughout his reign, Yogi Bhajan hobnobbed with the powerful, including encounters with President Nixon, two popes, and the Dalai Lama. The governors of California and New Mexico became his confidants, unaware of the web of deception he spun. Under his leadership, billion-dollar enterprises like Yogi Tea and Akal Security flourished. Such was the influence of this enigmatic figure that upon his passing in 2004, the American Congress honored him with a two-page resolution, while New Mexico inaugurated the "Yogi Bhajan Memorial Highway." However, it wasn't until the early 2020s, when a former leader of the 3HO community came forward with her testimony, that the truth began to emerge from decades of silence. Under the Yoga Mat reveals the harrowing experiences of hundreds of ex-3HO members, shedding light on the isolation, neglect, hunger, and abuse they endured in schools in India from a tender age. Shockingly, it is estimated that Yogi Bhajan sexually abused approximately 100 women, justifying his actions with the chilling statement, "Rape is always invited." At the heart of this extraordinary book lie the stories of these courageous 3HO survivors. Coenen's masterful narrative not only exposes the crimes themselves but also explores why a culture of silence persisted for so long, engendering fear and obedience among the followers. As the shadows of the past give way to the truth, their accounts serve as a rallying cry for justice and healing. With its compelling blend of investigative research, personal testimonies, and historical context, Under the Yoga Mat challenges our perception of spiritual leaders, champions the resilience of survivors, and sparks a critical conversation about power, manipulation, and the darker side of spiritual movements"--